(untitled) (Studia theodisca, 2017)
This article examines Andrea Balzola’s cross-media performance Le voci del vulcano (2012), which is a computer based interactive video installation dedicated to Friedrich Hölderlin, and Maria Giovanna Cicciari’s Hyperion (2014), an experimental film inspired by the name-sake German novel, as exemplary documents of the productive reception of Hölderlin’s life and work in Italy today.